The Patriarchal Culture in Michelle Kadarusman’s Girl of the Southern Sea: A Feminism Study - Ainun Nur Fitriani; Nurhayati Sulasih (Faculty of Social and Political Sciences University of Bangka Belitung, 2022)
This study aims to reveal the kinds of discrimination due to the patriarchal culture experienced by the protagonist in the novel Girl of the Southern Sea by Michelle Kadarusman. To expose the kinds of discrimination due to the patriarchal culture experienced by the protagonist, this study uses a qualitative method that refers to a descriptive approach to collect primary and secondary data as material for problem-solving and is what it is. This study uses feminist literary criticism theory as a data analysis tool. This research is essential to study because the patriarchal culture inherent in society is the cause of women experiencing discrimination. Men and women play patriarchal culture, so it is oftentimes for women to experience discrimination from men and fellow women. The results showed that Nia, the protagonist in the novel Girl of the Southern Sea, experienced several situations where she was marginalized, subordinated, and stereotyped by men and other women. If literature (novel) is considered a reflection of society, the novel Girl of the Southern Sea critically represents the idea.